Effects of Different Feedback Types and Answer Changing on Achievement of Tenth Grade Students - Wancham , Kittitas; Tangdhanakanond, Kamonwan (Journal of Education Studies, Chulalongkorn University, 2020)
This research aimed to (1) compare achievement among students provided with static feedback in the form of hints, reducing feedback with hints, and knowledge of response feedback, (2) compare achievement among students who did not get the opportunity to change answers with those who did get the opportunity to change answers, and (3) examine the interaction effect of feedback types and answer changing on achievement. We performed a 3 × 2 completely randomized factorial designs. Participants were 381 tenth-grade students whose selection was randomized by using a multistage sampling method. Two computerized tests comprising 10-item completion questions each were administered in this research. Two-way ANOVA was performed to analyze the data. The results showed that the main effect of feedback types was statistically significant at .05 levels, F(2, 375) = 8.52, p < .001, = .04. Similarly, the main effect of answer changing was statistically significant at .05 levels, F(1, 375) = 29.64, p < .001, = .07. However, the interaction effect was not statistically significant at .05 levels, F(2, 375) = 2.70, p = .07, = .01.